The Effectiveness of Quiz-Assisted Particle Dynamics E-Module in Practicing Problem-Solving Ability - Dina Selvia; Abdul Salam M; Surya Haryandi; Mohd Ali Ibrahim (Jurnal Ilmiah Pendidikan Fisika, 2023)
The lack of problem-solving skills students possess impacts the low completion of physics description questions in class. The purpose of this study is to determine the effectiveness of the e-module with the help of questions to train students' problem-solving skills that are suitable for use in learning activities in terms of their effectiveness in improving learning outcomes and achieving minimum completeness criteria. The type of research used is research and development using the ADDIE model, tested on 20 students of class X MIPA 2 Public High School in Banjarmasin. The data collection instrument used is the learning outcome test. The data analysis technique used is descriptive quantitative. The results showed that the electronic module was declared valid with an average validity score of 3.47 in the very good category, which was then continued at the field test stage to determine the effectiveness assessment of the electronic module so that it could be declared effective with an N-gain of 0.69 in the medium category. The research concludes that the electronic module developed is suitable for learning activities and can be applied to other learning.